Praktik manajemen keuangan pada kinerja usaha mikro-kecil, dan perbedaan peran gender - Triagita, Arinda; Tan, Emmelia (Jurnal Akuntansi dan Manajemen, 2025)
This study examines the impact of financial management practices, including working capital, financing, and budgeting, on the performance of Micro-Small Enterprises (MSEs), while testing for differences in gender roles within the research model. The study involved 143 MSEs in the food and beverage sector in Bekasi Regency, selected through purposive sampling. The results showed that financing and budgeting practices positively affected MSE performance, while working capital practices had no significant effect. Additionally, the empirical results revealed different gender roles in the relationship between financing and budgeting practices and performance. Specifically, female business owners had a positive impact on performance. This study contributes to the literature of financial management practices. Additionally, previous empirical studies have limitedly discussed the role of gender in MSEs' financial management practices in the food and beverage sector.